Prevalence of somatic and germline mutations of Fumarate hydratase in uterine leiomyomas from young patients. Issue 3 (13th January 2020) - Liu, Chengbao; Dillon, Jessica; Beavis, Anna L; Liu, Yuehua; Lombardo, Kara; Fader, Amanda N; Hung, Chien‐Fu; Wu, Tzyy‐Choou; Vang, Russell; Garcia, Jairo E; Xing, Deyin
Abstract : Aims: Hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome is caused by germline mutations in the Fumarate hydratase ( FH ) gene. In young women, the syndrome often presents with symptomatic uterine leiomyomas, leading to myomectomy or hysterectomy. In this study, we aimed to investigate the incidence and mutational profiles of FH‐negative leiomyomas from young patients, thus allowing for early identification and triage of syndromic patients for surveillance. Methods and results: We evaluated 153 cases of uterine leiomyomas from women aged up to 30 years for loss of FH expression by tissue microarray (TMA)‐based immunohistochemical staining. Mutational analysis of tumours with loss of FH was carried out by polymerase chain reaction (PCR) amplification of 10 exons within the FH gene and subsequent Sanger sequencing. The status of promoter methylation was assessed by bisulphite sequencing. Loss of FH protein expression was detected in seven (4.6%) of 153 tested uterine leiomyomas from young patients. All FH‐negative leiomyomas displayed staghorn vasculature and fibrillary/neurophil‐like cytoplasm. We found that six (86%) of seven FH‐negative tumours detected by immunohistochemistry harboured FH mutations, 50% of which contained germline mutations. In particular, the germline mutational rate in FH gene was 2.0% (three of 153 cases). Bisulphite sequencing analysis failed to detect promoter methylation in any of the seven tumours. Conclusion: Our study showed a relatively high rate of FH germline mutation in FH‐negative uterine leiomyomas from patients aged up to 30 years. While genetic mutations confer protein expression loss, epigenetic regulation of the FH gene appears to be unrelated to this phenotype.